Zrekultywowane składowisko odpadów komunalnych jako potencjalne źródło metali ciężkich w glebach = A reclaimed municipal waste landfill as a potential source of heavy metals in soils - Rolka, Elżbieta; Berk, Paulina; Klach-Chęcmanowska, Karolina; Kosiorek, Milena; Żołnowski, Andrzej C. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this study has been to evaluate the impact of a reclaimed municipal waste landfill, situated in the District of Dywity (the Province of Warmia and Mazury), on the presence of heavy metals in soils. To this aim, from the landfill cap and from the area adjacent to the landfill were taken 16 samples.
Keywords: składowisko odpadów komunalnych; rekultywacja; metale ciężkie; zanieczyszczenie gleb; municipial waste landfill; reclamation; heavy metals; soil pollution